Effects of oxidation and precursors (lysine, glyoxal and Schiff base) on the formation of Nε-carboxymethyl-lysine in aged, stored and thermally treated chicken meat - Suhong Huang; Xiaoli Dong; Yulong Zhang; Ming Huang; Yuandong Zheng (Food Science and Human Wellness)
Advanced glycation end products (AGEs) might pose health risks, and processing and storage could accelerate the generation of AGEs in meat. However, limited few reports indicated the changes of AGEs contents in meat during storage. In this study, the aim is to investigate the oxidation and precursors and their roles in the formation of Nε-carboxymethyl-lysine (CML) in raw and cooked chicken meat after post-mortem ageing and storage. As post-mortem ageing and storage time increased, the CML content in cooked chicken breast significantly increased from 1.81 mg/kg to 2.00 mg/kg during 0−6 h, and then decreased from 2.00 mg/kg to 1.80 mg/kg during 6 h−1 day, finally increased again during 1−7 days, while the CML contents of raw and cooked leg significantly and continuously increased from 1.78 mg/kg to 2.08 mg/kg. Furthermore, CML was extremely positively correlated with fat oxidation (R2 = 0.793, P < 0.01), protein oxidation (R2 = 0.917, P < 0.01) and glyoxal (R2 = 0.678, P < 0.05), and was negatively correlated with lysine (R2 = 0.536, P < 0.05). No significant correlation was observed between the Schiff base and CML.